Compositional engineering of VOPcPhO-TiO2 nano-composite to reduce the absolute threshold value of humidity sensors - Azmer, M.I.; Aziz, F.; Ahmad, Z.; Raza, E.; Najeeb, M.A.; Fatima, N.; Bawazeer, T.M.; Alsoufi, M.S.; Shakoor, R.A.; Sulaiman, K. (Elsevier, 2017)
This research work demonstrates compositional engineering of an organic-inorganic hybrid nano-composites for modifying absolute threshold of humidity sensors. Vanadyl-2,9,16,23-tetraphenoxy-29H,31H-phthalocyanine (VOPcPhO), an organic semiconductor, doped with Titanium-dioxide nanoparticles (TiO2 NPs) has been employed to fabricate humidity sensors. The morphology of the VOPcPhO:TiO2 nano-composite films has been analyzed by atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM). The sensors have been examined over a wide range of relative humidity i.e. 20–99% RH. The sensor with TiO2 (90 nm) shows reduced sensitivity-threshold and improved linearity. The VOPcPhO:TiO2 (90 nm) nano-composite film is comprised of uniformly distributed voids which makes the surface more favorable for adsorption of moisture content from environment. The VOPcPhO:TiO2 nano-composite based sensor demonstrates remarkable improvement in the sensing parameter when equated with VOPcPhO sensors.